2023
DOI: 10.1111/pace.14880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SGLT2 inhibitors on cardiovascular events in patients with atrial fibrillation: A systematic review and meta‐analysis of randomized controlled trials

Shiyue Zheng,
Yiwei Lai,
Chao Jiang
et al.

Abstract: BackgroundSodium‐glucose cotransporter 2 inhibitors (SGLT2i) is reported to reduce incident atrial fibrillation (AF) in patients with or without diabetes; however, its cardiovascular (CV) benefit for AF patients remains unclear.SSAimsTo investigate the effect of SGLT2i on the incidence of CV events in patients with AF.MethodsSix randomized controlled trials (RCTs) assessing the effects of SGLT2i on CV outcomes in patients with or without AF were included (PROSPERO: CRD 42023431535). The primary endpoint was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Large clinical trials and meta-analyses have investigated the role of SGLT2 inhibition in incident AF, but the results remain controversial [ 28 , 29 ]. A recent study has suggested that the treatment effects of SGLT2i were associated with a lower incidence of HF hospitalization in patients with AF [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Large clinical trials and meta-analyses have investigated the role of SGLT2 inhibition in incident AF, but the results remain controversial [ 28 , 29 ]. A recent study has suggested that the treatment effects of SGLT2i were associated with a lower incidence of HF hospitalization in patients with AF [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…SGLTis were strongly associated with a consistent reduction in the risk of HF hospitalization in patients with AF [RR: 0.76 (95%CI 0.69-0.84); P < 0.001]. Thus, the treatment effects of SGLTis were associated with a lower incidence of cardiovascular events, especially HF hospitalization, in patients with a history of AF[ 37 ].…”
Section: Af/atrial Flutter and Other Arrhythmiasmentioning
confidence: 99%
“…We have read with the article "Effect of SGLT2 inhibitors on cardiovascular events in patients with atrial fibrillation: A systematic review and meta-analysis of randomized controlled trials " by Zheng et al 1 The meta-analysis included six randomized controlled studies to evaluate the effects of Sodium-glucose The meta-analysis was derived from randomized clinical trials; however, access to personal data of patients in the included studies was limited. Since the patients could not be evaluated individually, whether the patients had AF and the duration and etiology of AF could not be categorized.…”
Section: Is It Effective Sglt2 Inhibitors For Every Af Patients?mentioning
confidence: 99%